2021
DOI: 10.1111/aos.15084
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Graves’ orbitopathy: a multicentre study

Abstract: Purpose: Graves' orbitopathy (GO) is a rare condition in children often considered to be a less severe condition than at an older age. The aim of our study was to analyse if there are any factors that distinguish paediatric from adult GO in order to provide guidelines for assessing and managing paediatric GO. Methods: Study design is a multicentre retrospective observational case series; 115 paediatric patients diagnosed with GO who visited our university medical centres in the Netherlands and Iran between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Eighty percent of patients had mild disease, 18.3 percent had moderate-severe disease and 1.7 percent had severe Graves' ophthalmopathy (GO). [21] In Chinese children with GO, lower eyelid retraction was the most common clinical sign (38.6%). [22] Young-age-of-onset GD differs from juvenile hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of patients had mild disease, 18.3 percent had moderate-severe disease and 1.7 percent had severe Graves' ophthalmopathy (GO). [21] In Chinese children with GO, lower eyelid retraction was the most common clinical sign (38.6%). [22] Young-age-of-onset GD differs from juvenile hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…More severe features such as optic nerve dysfunction and muscular restriction are very rare [21]. A recent multicenter study (the largest published to date on this subject) found that out of 115 pediatric patients with GO, 2 (1.7%) had severe disease [22]. However, a significantly larger percentage (21.7%) ultimately underwent orbital decompression once the disease had stabilized, for the main indication of persistent proptosis and its significant impact on QOL [22].…”
Section: Graves Orbitopathymentioning
confidence: 99%
“…As the condition progresses, TSH-receptor antibodies stimulate these receptors in orbital fibroblasts, which produce cytokines and glycosaminoglycans, to trigger lymphocyte and myofibroblast proliferation. 32 Then, as edema progresses, a patient may present with proptosis, movement restriction, and peribulbar swelling. However, pediatric patients tend to have more softtissue involvement than EOM implications.…”
Section: Ophthalmic Complicationsmentioning
confidence: 99%